[SOLVED] How to convert this function from javascript to python?

Issue

Does anybody know how to convert this javascript function to python ?

javascript:

function ding(t, a, e, n) {
  return t > a && t <= e && (t += n % (e - a)) > e && (t = t - e + a), t
}

This is my try on doing so:

def ding(t, a, e, n):
    return t > a and t <= e and (t + n % (e - a)) > e and (t = (t - e + a)), t

It returns a syntax error at the "=" in (t = (t - e + a)) and idk how to solve this right.

When giving it these values: ding(53, 47, 57, 97) it should return 50 in the original javascript function.

Solution

Does it have to be a one-liner? Why not just split it into a few lines:

def ding(t, a, e, n):
    if t > a and t <= e:
        t += n % (e - a)

        if t > e:
            t -= e - a
    
    return t
    
print(ding(53, 47, 57, 97)) # 50

Answered By – lusc stands with Ukraine

Answer Checked By – Mildred Charles (BugsFixing Admin)

Leave a Reply

Your email address will not be published.